Association of the Charlson index with risk classification, clinical aspects, and emergency outcomes - Ana Paula Santos de Jesus; Meiry Fernanda Pinto Okuno; Cassia Regina Vancini Campanharo; Maria Carolina Barbosa Teixeira Lopes; Ruth Ester Assayag Batista (SciELO, 2022)
Abstract Objective: To exam the association of the age-adjusted Charlson comorbidity index with the categories of risk classification, the clinical aspects, and the patient outcomes in the emergency department. Method: Cross-sectional, analytical study that analyzed the medical records of 3,624 patients seen in the emergency department. Charlson index scores greater than 2 showed a high rate of comorbidity (mortality risk). T-test and analysis of variance were applied in the analyses. Results: There was a significant difference between the Charlson comorbidity index and the risk classification, with higher scores found in patients classified in the white (2.57) and red (2.06) categories. Patients with vascular, endocrine, neurological, cardiologic, or device problems, and those who underwent a head tomography had a high rate of comorbidity. In addition, those admitted, transferred, or who died in the emergency room had significantly higher index scores compared to those who were discharged from the hospital. Conclusion: The high rate of comorbidity was associated with the categories of risk classification, main and nonspecific complaints, performance of a head tomography, and patient outcomes in the emergency room.